Efforts to Improve Fine Motor Skills of Early Childhood Through Science Games at RA An Nur Jogosatru Sukodono Sidoarjo - Rahmawati , Eny (MANDAILING GLOBAL EDUKASIA, 2024)
Science games are a learning activity or introduction to science that is adapted to the characteristics of early childhood children, where the delivery process is based on the principles of play (as one type of the concept of play). Fine motor skills are movements that only involve certain parts of the body and are performed by small muscles. Science toys are very supportive in improving the fine motor skills of early childhood children. But in reality, Children's fine motor development at RA AN NUR Jogosatru Sukodono Sidoarjo is only monotonous with the movement of holding pencils and crayons. Therefore, I will apply science games by packaging them in an interesting game concept, which is by inviting children to squeeze foam filled with water and paste leaves on picture paper so that children are more enthusiastic and interested in learning to improve children's fine motor skills at RA AN NUR Jogosatru Sukodono Sidoarjo. The purpose of this research is to apply science games in improving the fine motor skills of early childhood children at RA AN NUR Jogosatru Sukodono Sidoarjo. The method of data collection in this research is interview, observation and documentation. While the data analysis used is a qualitative descriptive analysis technique. The conclusion of this research is that the application of science games in improving the fine motor skills of early childhood children at RA AN NUR Jogosatru Sukodono Sidoarjo is very good so that the students are very happy and enthusiastic about learning.